Occurrence of, and yield response to, Russian wheat aphid, Diuraphis noxia (Hemiptera: Aphididae) in irrigated wheat in Ethiopia. (14th January 2015) - Damte, Tebkew
Abstract : The present study investigated the incidence and effect of the Russian wheat aphid (RWA) Diuraphis noxia (Kurdjumov) on irrigated wheat yield at Debre Zeit, Ethiopia. Wheat varieties were sown at the rate of 140 kg/ha on Vertisols on plots of 3 × 3 m. Treatments were tested in a split plot with varieties as the subplot and insecticide as the main plot, and were replicated three times. RWA appeared first when the crop reached the four- to five-leaf stage (Zadoks stage 22). In 2012 season, the RWA population peaked in the last week of March, and at this peak infestation, the average number of RWA per tiller was 46.9 on Denbi, 59.6 on Kubsa, 63.6 on Millennium and 56.2 on Werer. However, there were less than three RWA per tiller on sprayed wheat. In 2013, at the peak population intensity, there were 10.1, 10.5, 9.6 and 10.2 RWA per tiller on Denbi, Kubsa, Millennium and Werer, respectively. However, on sprayed wheat, the average population was less than one per tiller. The pattern of population build-up observed in the 2014 season was similar to that in 2013. Natural enemies of RWA were only a few generalist predators and were found at an extremely low density. In the 2012 season, avoidable loss in plant height, seed weight, grain number and grain yield ranged from 3 to 10%, 32 to 47%, 12 to 25%, and 69 to 93%, respectively. In the 2013 season, avoidable loss in seed weight and grain yield varied between 14 and 20%, and 15 and 41%, respectively. Similarly, in the 2014 season, avoidable loss in seed weight ranged between 9 and 24% and in grain yield between 35 and 49%.